The outcome of oncoplastic techniques in defect reconstruction after resection of central breast tumors. Issue 1 (December 2015) - Farouk, Omar; Attia, Essam; Roshdy, Sameh; Khater, Ashraf; Senbe, Ahmad; Fathi, Adel; Hamed, Emad-Eldeen; Mesbah, Mahmoud; Shehatto, Fayez; El-Saed, Aiman; Denewer, Adel
Abstract Background Traditionally, conservative breast surgery was contraindicated in centrally located breast tumors, with total mastectomy as the treatment of choice. However, restorations of the central defects by the oncoplastic volume displacement or replacement techniques have been shown to be effective. The aim of the current study was to assess the surgical outcome of oncoplastic techniques after central breast tumors resection. Methods Thirty patients with central breast cancer, including two patients with Paget disease, treated at the Oncology Center of Mansoura University (Egypt) between June 2011 and December 2014 were included in this study. The oncoplastic techniques performed were Grisotti advancement rotational flap in eight (26.7 %) patients, classic skin-sparing mastectomy (SSM) with latissimus dorsi pedicled flap in 20 (66.7 %) patients, and skin-reducing mastectomy (SRM) with latissimus dorsi pedicled flap using wise pattern inverted T incision in two (6.7 %) patients. The choice of the oncoplastic techniques depends on the achievement of free safety margins, the breast volume, and its ptotic degree. Results The median age was 40.5 years (range; 23–55). There were no major complications that require repeating the oncoplastic techniques. Recorded complications included wound dehiscence (4/30, 13.3 %) donor site seroma (4/30, 13.3 %), and surgical site infection (1/30, 3.3 %). The 6-month subjective patient satisfaction was excellent in 21 (70 %) patients, good in 6 (20 %) patients, and fair in 3 (10 %) patients. There was no episode of local recurrence or systemic metastasis after an average follow-up duration of 24 months (range; 6–42). Conclusions Restoring the central defect after resection of the central breast tumors can be safely achieved using oncoplastic procedures including the Grisotti technique or the design of SSM or SRM with immediate breast reconstruction. In our patients, these procedures yield a satisfactory esthetic outcome with lower morbidity.